2007
DOI: 10.4081/jae.2007.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach for Determining Hydrologic Behavior and Depth of Soils at Basin Scale

Abstract: Land-surface models at basin scale usually employ various combinations of land-use and soil class data to parameterize the major hydrologic processes. Even though soil exerts a major influence on hydrologic processes, soil hydraulic behavior is still difficult to quantify at relatively large scales. Recently soil hydraulic parameterization for hydrologic modeling can be conveniently carried out using pedotransfer rules, which are based on the knowledge of basic soil physical and chemical variables, such as bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additional information about land cover features and hydraulic properties characteristics of the soils in the Fiumarella catchment are available elsewhere (Santini et al, 1999;Romano and Palladino, 2002;Fiorentino et al 2006;Carriero et al, 2007). …”
Section: Site Descriptionmentioning
confidence: 99%
“…Additional information about land cover features and hydraulic properties characteristics of the soils in the Fiumarella catchment are available elsewhere (Santini et al, 1999;Romano and Palladino, 2002;Fiorentino et al 2006;Carriero et al, 2007). …”
Section: Site Descriptionmentioning
confidence: 99%
“…This shows that the importance of vegetation in forecasting soil depth in the study area, which has also been reported by previous researchers (Tesfa et al, 2009;Gastaldi et al, 2012;Seid et al, 2013). Carriero et al (2005) showed that there was a fairly good correlation between soil depth and slope gradient, wetness index and mean annual precipitation for the study basin. They showed that this correlation can be improved, if information about vegetation characteristics is added.…”
Section: Model Evaluationmentioning
confidence: 95%
“…Catchment pedology was investigated through field campaigns and laboratory measurements aimed at identifying the main soilland units of the basin. These data were reported in the land cover map elaborated by Santini et al (1999) that was there after used by Carriero et al (2007) to define the soil hydraulic properties of each unit. Such an analysis was used in the rainfall-runoff application that requires accurate information about the spatial variability of soils (Romano and Santini, 1997;Romano and Palladino, 2002).…”
Section: Study Area and Experimental Setupmentioning
confidence: 99%